Pain management in interventional radiology - Ray, Charles E. (Cambridge medicine, 2008)
As interventionalists become more involved with patients as care providers rather than solely as proceduralists, understanding and treating pain is a vital part of daily practice. This book provides an overview of the multiple techniques used in the management of pain in interventional radiology suites. Topics include techniques for the treatment and prevention of pain caused by interventional procedures, as well as minimally invasive techniques used to treat patients with chronic pain symptoms. Approximately half of the book is dedicated to the diagnosis and treatment of spinal pain; other chapters focus on intraprocedural and post-procedural pain management, embolization and ablation techniques used to treat patients with uncontrollable pain, and alternative treatments for pain relief. This book is a practical resource for anyone looking to acquire skills in locoregional or systemic pain control and wishing to improve the quality of life for patients undergoing procedures or suffering from disease-related pain